(untitled) (Training and Practice : Journal of Educational Sciences, 2010)
The article deals with one of the most important aspects in L2 teaching methodology: the importance of cultural issues in language teaching curricula. Most attempts to set out the aims of Foreign Language Teaching include among the goals of a cultural component. ‘How should I include culture into teaching a language?’ - a language teacher asks. There is one main answer, and all the minor answers derive from that: use authentic materials. It is difficult to escape teaching culture if you use authentic documents. As soon as language learners come across something they do not understand – not linguistically, but from behavior viewpoint – the teacher has to explain the cultural background to provide deep understanding. By teaching about cultures we do not mean “lecturing” in a dull way about some events, places and people our students probably do not care about. We mean to apply active, interesting activities centered on being correctly understood.